Primary Cerebral Radiotherapy-Induced Rhabdomyosarcoma: Treatment with Intraoperative Carmustine Implants. (18th January 2013) - Rivero-Garvía, Mónica; Márquez-Rivas, Javier; Rivas, Eloy; Medina-López, Diego; Quiroga-Cantero, Eduardo
Abstract : Introduction : Primary cerebral rhabdomyosarcomas (cRMS) are extremely rare, with only 41 cases reported in the literature. Survival of patients with localized cRMS is 70% after 5 years but not in the case of intracranial neoplasms, where survival rarely exceeds 10 months. Case report : A 10-year-old female patient with a history of acute lymphoblastic leukemia (ALL) and holocranial radiotherapy (RT) 6 years ago, referred after partial surgical resection of a left parietal lesion, diagnosed as an embryonal tumor with mixed neuronal-glial differentiation (WHO grade IV). A second operation was performed for complete resection and placement of intracavitary chemotherapy (carmustine). The pathology revealed a high-grade undifferentiated neoplasm positive for myogenin and desmin that was compatible with cRMS. In the immunohistochemistry study, the neoplasm was positive for vimentin, myogenin, and desmin, as is characteristic of cRMS, and negative for synaptophysin and enolase, ruling out primitive neuroectodermal embriogenic tumor (PNET). Given a diagnosis of cRMS, a combined thoracoabdominal PET-CT scan was performed without finding other primary lesions and a bone marrow study was also performed without observing abnormalities. Consequently, the diagnosis was established as primary cRMS. Discussion : Among the long-term sequelae of radiotherapy, neurocognitive disorders, brain disorders such as leukomalacia, vascular diseases, or secondary tumors, ranging from benign lesions such as meningiomas to more aggressive lesions such as ependymomas, which are high-grade gliomas, are described. In the brain MRI, our patient showed a radiotherapy-induced periventricular leukomalacia and a malignant lesion: a cRMS. The use of carmustine in this disease may facilitate local control.